Penyuluhan Hukum Bahaya Narkoba bagi Generasi Muda di Desa Sindangagung, Kuningan - Pina Pina; Nur Aisyah Sintawati; Ega Fahril Fadilah; Mochamad Riski Maulana; Fajar Octavian Nugraha; Roehan Akbar; Suwari Akhmaddhian; Iman Jalaludin Rifai; Dikha Anugrah (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
In carrying out legal awareness within the community itself, legal counseling is very necessary in order to achieve high legal awareness in society. Such counseling must be strengthened, so that every member of the community is aware of and lives up to their rights and obligations as citizens in the framework of law enforcement, justice and the protection of human dignity. This legal counseling aims to implement student learning outcomes in the world of lectures and increase understanding of their studies so that they can be applied or disseminated to the public through legal counseling. The first stage is the preparatory stage. At this stage, lecturers and students have prepared materials related to narcotics and legal aid.The next second stage is the stage of implementing material delivery activities to the community as a form of counseling. At this stage the lecturer provides legal aid material and students will provide material about the dangers of drugs. The last third stage is a question and answer session about the material presented by the resource persons. Counseling efforts in Sindangagung Village, Sindangagung District, Kuningan Regency which were carried out on February 8, 2023. This agenda was carried out as an effort to provide understanding to the community and village officials about the increasingly widespread dangers of drugs and legal assistance for people who need the services available at the Faculty. Kuningan Law University, namely the Center for Consultation and Legal Aid for PKBH.